101 African Americans Who Shaped South Carolina - Powers, Bernard E., Jr (Book collections on Project MUSE., 2020)
"This collection gathers entries previously published as part of the South Carolina Encyclopedia. Each entry offers a thumbnail description of an African American figure with a connection to South Carolina who made a significant impact in the history of the state, nation, and, in some cases, world. While most entries discuss a single individual, six discuss events or collections of people whose actions had a significant role in shaping South Carolina"--